Global citizenship: A new and vital force - Michelle Bachelet (UN Chronicle, 2018)
The idea of global citizenship goes back a long way, but in its current iteration it played its most significant role in the process that began with the creation of the United Nations in 1945 and the adoption of the Universal Declaration of Human Rights in 1948, continuing with the adoption of the Sustainable Development Goals and the Paris Agreement in 2015. This has been a period during which lessons were learned, tragedies were experienced and progress was made and during which the idea and the institutions promoting an inherent and universal dignity of the human person gradually matured.